2016
DOI: 10.21037/atm.2016.10.04
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of surgical telementoring: current applications and future directions

Abstract: Surgical telementoring is a concept within telemedicine that involves the use of information technology to provide real-time guidance and technical assistance for surgical procedures from an expert physician at a different geographical location. It is a means to overcome the logistic obstacles associated with traditional mentoring and can aid in the distribution of advanced surgical techniques. In addition to its perceived educational benefits, it has the potential to directly impact patient care by providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The application of telemedicine should be guided by the same ethical principles upon which medi-providing this service(10) with surgical robots and joint development projects have appeared in recent years (11). Several review studies on the application of telementoring in mini-invasive surgery have been published, and concluded that it is a safe and effective procedure that is comparable to face-to-face mentoring (12)(13)(14)(15)(16)(17).…”
Section: Telemedicine Ethics and Ethical Guidelinesmentioning
confidence: 99%
“…The application of telemedicine should be guided by the same ethical principles upon which medi-providing this service(10) with surgical robots and joint development projects have appeared in recent years (11). Several review studies on the application of telementoring in mini-invasive surgery have been published, and concluded that it is a safe and effective procedure that is comparable to face-to-face mentoring (12)(13)(14)(15)(16)(17).…”
Section: Telemedicine Ethics and Ethical Guidelinesmentioning
confidence: 99%
“…Development of mentoring programs through the use of telemedicine could be of great interest in the future from several points of view. First, by addressing this method, the difficulty in providing health care to people from disadvantage areas that do not have access to specialized, healthcare institutions could be overcome [14]. Moreover, a highly specialized level of surgical act could be offered by surgeons with less experience in a particular field.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is typically used to diagnose and monitor patients in rural settings and in prisons and typically refers to an encounter between provider and patient . In contrast, “telementoring” refers to a provider‐to‐provider relationship and has more often been applied to surgical specialists who provide assistance to surgeons in remote locations including battlefields and underserved, rural areas . Telementoring is essentially real‐time technical assistance and guidance between a provider with specialized information and a remote provider who is the recipient of the information .…”
Section: Introductionmentioning
confidence: 99%